2016
DOI: 10.1519/jsc.0000000000001374
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Alters the Bone Mineral Density of Hemodialysis Patients

Abstract: Marinho, SM, Moraes, C, Barbosa, JEdSM, Eduardo, JCC, Fouqe, D, Pelletier, S, and Mafra, D. Exercise training alters the bone mineral density of hemodialysis patients. J Strength Cond Res 30(10): 2918-2923, 2016-Patients with chronic kidney disease undergoing hemodialysis (HD) frequently present low bone mineral density (BMD), and exercise may be useful for treating bone loss. This study aimed to assess the effects of an intradialytic resistance exercise training program (RETP) on BMD in HD patients. Twenty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
4
26
0
3
Order By: Relevance
“…There is a general consensus that intradialytic ET is safe, 57 , 58 and our study supported the safety of intradialytic ET and intradialytic CT. As might be expected, previous studies demonstrated an impact of intradialytic ET (i.e., physical exercise) on physical findings, including physical function, 45 , 46 , 50 treatment-related symptoms, 59 dialysis efficacy, 60 inflammation, 45 bone mineral density, 45 , 47 quality of life, 48 peak oxygen consumption, 49 , 50 anxiety, 51 and exercise capacity. 61 We extended these studies to test the impact of physical exercise on cognitive findings (i.e., intradialytic ET preserves cognitive function).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…There is a general consensus that intradialytic ET is safe, 57 , 58 and our study supported the safety of intradialytic ET and intradialytic CT. As might be expected, previous studies demonstrated an impact of intradialytic ET (i.e., physical exercise) on physical findings, including physical function, 45 , 46 , 50 treatment-related symptoms, 59 dialysis efficacy, 60 inflammation, 45 bone mineral density, 45 , 47 quality of life, 48 peak oxygen consumption, 49 , 50 anxiety, 51 and exercise capacity. 61 We extended these studies to test the impact of physical exercise on cognitive findings (i.e., intradialytic ET preserves cognitive function).…”
Section: Discussionsupporting
confidence: 71%
“…Exclusion criteria included angina pectoris, chronic lung disease, cerebral vascular disease, musculoskeletal or orthopedic conditions limiting physical activity, lower or upper extremity amputation, decreased mental capacity, or diagnosed dementia, consistent with previous exercise intervention studies of HD patients. 45 , 46 , 47 , 48 , 49 , 50 , 51 We approached 27 HD patients, and 1 was not eligible. Of the 26 patients identified as eligible, 23 agreed to participate, and 20 were available for follow-up at 3 months (the other 3 changed dialysis centers during the study and were excluded) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although RT has been applied in HD patients across different studies, there is no consensus concerning its use in these patients (8,11). Chronic kidney disease patients, undergoing hemodialysis frequently, present low bone mineral density (BMD); a study showed that resistance exercise could improve the BMD of HD patients (12). Another study found that the acute effect of resistance exercise in HD patients could increase the acyl-gherlin (the hunger hormone) and decrease obestatin (the hormone that leads to feeling full) levels, which means it could be beneficial for increasing the appetite of these patients, which was another problem for them (13).…”
Section: Introductionmentioning
confidence: 99%
“…Otro beneficio del ejercicio, en particular el de resistencia, es su utilidad para mejorar la densidad mineral ósea en pacientes en HDC, describiéndose en un estudio experimental una reducción significativa del porcentaje de osteoporosis en el grupo que realizó ejercicio 36 . También se han comunicado beneficios de programas de ejercicio intradiálisis adaptados para pacientes ancianos con alta comorbilidad en HDC (mayores a 75 años), observando mejoras significativas en la fuerza muscular, capacidad funcional, sintomatología depresiva y calidad de vida relacionada a salud (CVRS) 37 .…”
Section: Beneficios Del Entrenamiento Físico En Pacientes Con Erc Avaunclassified